Amorphous Cobalt Iron Borate Grown on Carbon Paper as a Precatalyst for Water Oxidation. Issue 15 (3rd July 2019) - Liu, Huibing; Yang, Liu; Qiao, Kangwei; Zheng, Lirong; Cao, Xiaohua; Cao, Dapeng
Abstract: The key to improving water oxidation is to develop efficient and earth‐abundant catalysts for the oxygen evolution reaction (OER). Herein, a new amorphous cobalt iron borate supported on 3D carbon paper integrated electrode is reported as a precatalyst for the OER, which was synthesized by using a one‐pot hydrothermal method. An optimum OER activity was obtained at 25 % Fe doping by screening the compositions of the Co and Fe. The best synthesized catalyst needs an overpotential of 227 mV to deliver a current density of 10 mA cm −2 and also exhibits a long‐term durability of 24 h. Impressively, we find that CoFe oxyhydroxide was formed in situ in the OER process, which serves as the real catalytic active species for OER. Moreover, the direct conversion from CoFe borate to CoFe oxyhydroxide is reported for the first time in metal borate OER catalysts. The discovery in this work, that is, that metal borate as a precursor can efficiently catalyze the OER in alkaline media, significantly widens the family of OER catalysts. Abstract : Grown on paper : A new amorphous cobalt iron borate supported on 3D carbon paper integrated electrode is reported as a precatalyst for water oxidation. The optimized oxygen evolution reaction (OER) activity is obtained by screening the Co and Fe compositions, and the CoFe oxyhydroxide in situ formed in the OER process is revealed to be the real catalytical active species for OER.